Effect of replacing chicken meat and adding oats L. Avena sativa on the physical and sensory characteristics of veal patties (Journal of the College of Basic Education, 2022)
The current study aimed to find out the effect of adding 10% oat powder to a mixture of minced meat tablets, in which chicken meat was replaced with pure veal meat, in five ratios of 100, 75, 50, 25.0%, on the physical and sensory characteristics of the processed meat tablets. Results showed The current study showed a significant increase in the percentage of losses during cooking by increasing the percentage of substituting chicken meat, and a significant decrease with the addition of 10% oats to the meat patties, by increasing the percentage of substituting chicken meat for pure veal meat.